2011
DOI: 10.5688/ajpe7519
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-based Medicine Elective Course to Improve Student Performance in Advanced Pharmacy Practice Experiences

Abstract: Objective. To implement and evaluate the impact of an elective evidence-based medicine (EBM) course on student performance during advanced pharmacy practice experiences (APPEs). Design. A 2-hour elective course was implemented using active-learning techniques including case studies and problem-based learning, journal club simulations, and student-driven wiki pages. The small class size (15 students) encouraged independent student learning, allowing students to serve as the instructors and guest faculty members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 10 publications
2
40
0
3
Order By: Relevance
“…More than 86% of preceptors surveyed agreed that students who completed the elective course 1 had stronger evidence-based medicine skills than nonparticipants. 7 An active-learning approach to assessment of landmark trials and application of findings to patient care decisions increased students' comfort with the technical aspects of using evidence-based medicine skills to evaluate literature in a third-year elective course. 8 The evidence-based approach to patient care is becoming more widely recognized, and the decision-making process regarding therapeutic choices can be approached similarly with a population perspective such as formulary management of prescription drugs.…”
Section: Introductionmentioning
confidence: 99%
“…More than 86% of preceptors surveyed agreed that students who completed the elective course 1 had stronger evidence-based medicine skills than nonparticipants. 7 An active-learning approach to assessment of landmark trials and application of findings to patient care decisions increased students' comfort with the technical aspects of using evidence-based medicine skills to evaluate literature in a third-year elective course. 8 The evidence-based approach to patient care is becoming more widely recognized, and the decision-making process regarding therapeutic choices can be approached similarly with a population perspective such as formulary management of prescription drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by incorporating good understanding of research and statistical evidence into this rotation one would expect the gained students' knowledge and clinical expertise to facilitate a full comprehension of the published therapeutic protocols which the preceptors of this rotation had intended to review systematically. This notion was supported in the pharmacy literature where using active learning techniques, journal club, and literature evaluation exercises improved the performance of students on APPE rotations [2].…”
Section: Introductionmentioning
confidence: 72%
“…Bookstaver and colleagues described the development of an evidence-based medicine elective course (2 hours per week for 1 semester, 15 students per class) to improve student performance in APPEs. 6 The course used case studies, journal club simulations, and student-driven wiki pages to improve students' literature evaluation skills and ability in applying clinical evidence to practice. Experiential preceptors reported that students who had completed the course had stronger skills in applying evidence-based medicine to patient care than other students.…”
Section: Discussionmentioning
confidence: 99%